Integrating Publuu technology into interactive teaching materials as a strengthening of evaluation material learning in the Teacher Professional Education Program (PPG) - Wahyudi, Adip; Arifin, Slamet; Mutia, Tuti; Hasporo, Cahyo Aji; Maulana, Feri Fahrian; Fadani, Hikmah Al; Putra, Halil Haqizul (Universitas Negeri Yogyakarta, 2025)
Learning in the digital era requires innovative interactive media to improve educational effectiveness, including learning evaluation. The main challenge is low student engagement due to conventional evaluation methods. Publuu, an interactive digital platform, offers a solution by providing interesting teaching materials. This study developed and tested Publuu-based interactive materials for learning evaluation courses in the Teacher Professional Education (PPG) program. Using the ADDIE-based Research and Development (R&D) method, data were collected through initial trials and final trials on two groups: the experimental group (30 students using Publuu) and the control group (30 students using conventional methods). Normality and homogeneity tests ensured statistical validity, followed by paired sample t-tests. The results showed that Publuu materials significantly improved student learning outcomes, with a significance value (Sig.) <0.05. In addition, these materials increased student motivation and engagement. Thus, Publuu-based interactive learning materials are suitable for PPG programs, improving the quality of evaluation learning. This study provides practical benefits of interactive tools in improving learning effectiveness and student active participation. Future developments may include more interactive features to increase the appeal and effectiveness of the material.